Influence of film morphology and crystallinity on charge carrier concentration-dependent hole mobility in hexamethyldisilazane treated Pentacene bottom contact devices. (19th August 2021) - Jena, Sanjoy; Rajpoot, Anuj; Dutta, Soumya; Ray, Debdutta
Abstract: The effect of substrate temperature and deposition rate on the film morphology, crystallinity, and electronic properties of Pentacene transistors treated with hexamethyldisilazane (HMDS) is studied. The gate bias dependence of mobility is used to estimate the width of the density of states and thereby quantify the disorder of the highest occupied molecular orbital. A low deposition rate and the substrate held at room temperature are shown to be the optimal conditions for good mobility (0.20 cm 2 V −1 s −1 ) and low electronic disorder (50 ± 10 meV). X-ray diffraction measurements are performed to quantify the ratio of the two crystalline phases (thin-film phase and bulk phase) present in the film. The crystalline phases, rather than grain size, plays a significant role in determining the charge carrier mobility. Film deposition with the substrate at room temperature leads to low electronic disorder as the film is composed of one crystalline phase (thin-film phase), while high substrate temperature makes the film increasingly polymorphic, leading to increased electronic disorder (up to 230 meV). A high deposition rate leads to poor morphology of Pentacene near the source/drain electrode edge, thereby leading to increased contact resistance and electronic disorder. Hence, a low growth rate at room temperature is required for HMDS treated substrates to induce good crystalline properties of the film in the channel region, which results in enhanced electronic properties of the transistors.